Estudo de probabilidade utilizando o jogo do bingo no Ensino Médio - Guimarães, Suzy Corrêa (Brasil, 2023)
The present work aims to present an unprecedented class, based on a differentiated methodology, aiming to help students to understand Probability and to encourage teachers to work with playfulness. The chosen methodology was the gamification through the game of chance, using the Bingo Game. The class was applied in the city of Manaus, in a State school, with 21 students of the 1st year of High School. The results indicated that the applied methodology was well accepted by the students, contributing to the elaboration of the concept of probability. However, for a more meaningful learning, it is necessary a longer time and the application of other games to reinforce the study of the ludic with the probability.